2019
DOI: 10.1080/13603116.2019.1572797
|View full text |Cite
|
Sign up to set email alerts
|

The transition experiences of students with disabilities moving from primary to secondary schools in NSW, Australia

Abstract: This paper investigates the transition experiences of students with intellectual disability, as they move from primary to secondary school in New South Wales, Australia. Employing a multiple case study approach, the authors investigated the transition from the perspective of the students experiencing it. During the study, ten students with mild to moderate intellectual disability participated in interviews and were observed in the school environment before and after they transitioned from primary school to sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It would be impossible to explore the transition experiences of the young people in this research without reference to the ontological reality of their likely difficulties with social interaction and understanding The methods developed were designed to move away from a deficit model of autism to privilege autistic students' experience of transition as few studies incorporate their perspectives (Pitt et al 2019;Nind and Vinha, 2013). Methods therefore included a variety of approaches including 'interrupted interviews' with the young people (Shepherd 2015) to take account of their potential antipathy towards intense face-to-face interviews with a relative stranger (the researcher).…”
Section: Methodsmentioning
confidence: 99%
“…It would be impossible to explore the transition experiences of the young people in this research without reference to the ontological reality of their likely difficulties with social interaction and understanding The methods developed were designed to move away from a deficit model of autism to privilege autistic students' experience of transition as few studies incorporate their perspectives (Pitt et al 2019;Nind and Vinha, 2013). Methods therefore included a variety of approaches including 'interrupted interviews' with the young people (Shepherd 2015) to take account of their potential antipathy towards intense face-to-face interviews with a relative stranger (the researcher).…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured interviews utilize a pre-determined interview schedule but allow for flexibility according to participant answers and can elicit rich information and insight (Martin et al, 2019). They can be an effective method for working with children (Greig et al, 2007), as the flexibility of the interview removes the need to stay 'on topic' and allows for the emergence of new topics (Pitt et al, 2021). Semi-structured interviews allow the participant and the researcher to work together to co-create meaning, thus encouraging participatory practice (Kara, 2015), and have been used effectively in studies investigating and amplifying the experiences and voices of autistic children and young people (e.g., Calder et al, 2013;Hamilton et al, 2023;Howard et al, 2019;Malloy et al, 2020).…”
Section: Semi-structured Interviewmentioning
confidence: 99%
“…The results of a study conducted on a group of teachers to find out their attitudes towards transitional planning for the post-secondary stage indicated that although teachers feel the importance of transitional planning, they find it difficult to integrate teaching self-determination skills with the core curriculum and more than half of the respondents referred to the extent of post-secondary transition planning (Wallen, 2014). Another study identified several factors that contribute to the success of the transition, namely helping students learn about, control, and manage the environment, building positive relationships with teachers, and obtaining additional support from teams working with them (Pitt et al, 2021).In addition, the professional guidance and planning for students with intellectual disabilities is limited compared to what is provided in public schools. There is a lack of adequate guidance for these students in integration schools, and there is a lack of clarity among the school staff about who is responsible for the transfer of students in many cases (Aston et al, 2021).…”
Section: Mahmoud Mohamed Eltantawymentioning
confidence: 99%
“…The results of one of the reviews that dealt with the importance of transitional programs for students with disabilities indicated the significance of the programs offered to them and that these programs have potentially positive effects on independent living and social life (Cobb et al, 2013). The results of some studies that examined the transition of students with intellectual disabilities from one stage to another indicated these students generally enjoy a pos-itive transition experience and that they also face many significant challenges, represented in problems related to schoolwork management, homework, and bullying (Pitt et al, 2021). Many factors can facilitate students' meaningful participation in transitional planning for graduation and success at the post-school stage.…”
Section: Mahmoud Mohamed Eltantawymentioning
confidence: 99%